DISTRIBUTION OF VIBRIO CHOLERA IN URBAN AREAS OF IRAQ - Arkan Altayar, Mostafa; Bassim Rasul Aldbagh, Mayyada; Habeeb Al-Hilfi, Kareema (Journal of Medical Genetics and Clinical Biology, 2024)
Objective: This study aims to examine the distribution, epidemiological characteristics, and public health response to Vibrio cholerae outbreaks in urban areas of Iraq. Method: The research employed a literature-based analysis supported by epidemiological surveillance data, case reports, and antibiotic resistance profiles, focusing on outbreaks from 2003 to 2022. Results: Findings reveal recurring cholera outbreaks with seasonal peaks during summer months, primarily affecting regions such as Baghdad and Sulaymaniyah. Demographic analysis indicates a higher prevalence among individuals aged 15–44, with variability in gender distribution across regions. The bacteria showed sensitivity to Ciprofloxacin and Tetracycline, while oral cholera vaccination (OCV) campaigns demonstrated high effectiveness in refugee and internally displaced populations. Novelty: This study offers a localized, data-driven understanding of cholera’s urban distribution in Iraq, highlighting the integration of demographic trends, antibiotic resistance, and the role of vaccination campaigns—an approach that remains underrepresented in existing regional literature. These insights are essential for developing more targeted and effective public health strategies.